Layered security model through integration of Vigenere and Hill Cipher in digital message encryption - Ramadhani, Argia Putri; Tami, Nanda Putri; Lestari, Asih; Erkamim, Moh (Journal of Information System and Application Development, 2024)
The rapid development of digitalization has a significant impact on data and information protection. One approach to protecting data and information is through the use of cryptography. The research aims to combine the use of Vigenere and Hill Cipher algorithms in modeling to maintain the security and confidentiality of digital messages. The focus of this research is on the process of encrypting digital text messages. The layered security in this study takes advantage of the advantages of each algorithm. The combination of the two is designed to increase the complexity of encryption and reduce vulnerability to cryptanalytic attacks. The encryption process starts with using Vigenere Cipher for initial message encrypting, then the results are re-encrypted using Hill Cipher. Research shows that this layered security model can improve data security and make it more difficult for uninterested parties to decipher it. The combination of Vigenere's and Hill Cipher's algorithms could be one of the layered security alternatives to digital message encryption in an effort to protect information and data from security threats in the digital age.